Effect of molecular weight on Piezoelectric properties of electrospun polyvinylidene fluoride blended with cellulose nanocrystals - Aminatul Sobirah, Zahari (2022)
Polyvinylidene fluoride (PVDF) has become widely used as a piezoelectric material in sensors, actuators, filters, and medical equipment. It is in high demand in industries owing to its high-quality features such as high flexibility, low cost, and light weight. PVDF is available in five types of crystalline phases, namely